Proceedings of the 2005 ACM Symposium on Applied Computing 2005
DOI: 10.1145/1066677.1066734
|View full text |Cite
|
Sign up to set email alerts
|

An interactive evolutionary algorithm for cochlear implant fitting

Abstract: In a previous SAC-COMPAHEC paper[1], a method was presented using an interactive evolutionary algorithm for cochlear implants fitting.The method has recently been put to test, with very unexpected and encouraging results: in a few words, it seems that the algorithm is capable to obtain much better results than an expert practitioner in many cases.The solutions proposed by the algorithm are counter-intuitive, yet they improve speech recognition drastically. If these preliminary results are confirmed by many mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…thesis of the Université de Bourgogne. These results have already been presented in several papers [6,7,8].…”
Section: Methodssupporting
confidence: 77%
“…thesis of the Université de Bourgogne. These results have already been presented in several papers [6,7,8].…”
Section: Methodssupporting
confidence: 77%
“…Previous studies had proposed optimization algorithms for customizing hearing aids (Durant et al, 2004;Kuk and Pape, 1992;Neuman et al, 1987;Preminger et al, 2000;Stelmachowicz et al, 1994) or cochlear implants (Bourgeois-République et al, 2005;Wakefield et al, 2005) with real patients. Even though the simulation results of the present study would be applicable specifically to the GA implementation reported by Başkent et al (2007b), similar simulations could be used to characterize the effects of differing user skills on how well any perceptual optimization method might work for general population.…”
Section: Resultsmentioning
confidence: 99%
“…The modified simplex algorithm was proposed for fitting gain in hearing aids (Kuk and Pape, 1992;Neuman et al, 1987;Preminger et al, 2000;Stelmachowicz et al, 1994). Genetic algorithms (GAs) were suggested for fitting features related to hearing aids (Durant et al, 2004) or cochlear implants (Bourgeois-République et al, 2005;Wakefield et al, 2005). In such perceptual optimization, candidate parameter sets are first evaluated by a listener and then modified according to listener's preferences following the rules of the particular method used.…”
Section: Introductionmentioning
confidence: 99%
“…We can also mention work in combining human interactions with an artificial ant, applied to non-photorealistic rendering [15]. Another use of IEC involves a human patient using a PDA on which an IEC is launched to define best parameter values for cochlear implants [2]. First results show that patients using PDAs obtain a better parameterization than previously through lengthy interaction with a doctor.…”
Section: Iec Related Workmentioning
confidence: 99%